Kombinasi Metode ROC dan Metode MAUT dalam Pemilihan Guru pada Madrasah Ibtidaiyah - II, Ramadani; Pristiwanto, Pristiwanto; Hasan, Yasir (Bulletin of Data Science, 2022)
Madrasah Ibtidaiyah Nurul Hidayah, Bandar Khalipah District, is one of the formal education infrastructure under the guidance of the Minister of Religion whose learning process is based on Islam at the elementary school level. This school is in need of Indonesian language teachers. The teacher is a teacher of a science and the teacher in general is a professional educator who has the main task of educating, directing, guiding, training, assessing, and evaluating his students, so in this case the author wants to help the school in the selection of Indonesian language teachers in Madrasah schools. Ibtidaiyah Nurul Hidayah, whose recruitment is still fairly manual. In this study the author has a solution and will solve the problem by applying the Rank Order Centroid (ROC) method and the Multy Attribute Utility Theory (MAUT) method, the author will combine the two methods to determine the best alternative in the selection of Indonesian language teachers in Madrasahs. Ibtidaiyah Nurul Hidayah. The results of the algorithm on the combination of the two methods show that Alternative 5 (A5) has the highest score of 0.832 and ranks 1, thus A5 is the best alternative that will be recommended for teacher selection at Madrasah Ibtidaiyah Nurul Hidayah. The application by combining the Rank Order Centroid (ROC) method and the Multi Attribute Utility Theory (MAUT) method can determine the best alternative in terms of teacher selection.